On the finite-size effects in two segregated Bose-Einstein condensates restricted by a hard wall - Quyet, H.V.; Thu, N.V.; Tam, D.T.; Phat, T.H. (Condensed Matter Physics, 2019)
The finite-size effects in two segregated Bose-Einstein condensates (BECs) restricted by a hard wall is studied
by means of the Gross-Pitaevskii equations in the double-parabola approximation (DPA). Starting from the consistency between the boundary conditions (BCs) imposed on condensates in confined geometry and in the full
space, we find all possible BCs together with the corresponding condensate profiles and interface tensions. We
discover two finite-size effects: a) The ground state derived from the Neumann BC is stable whereas the ground
states derived from the Robin and Dirichlet BCs are unstable. b) Thereby, there equally manifest two possible
wetting phase transitions originating from two unstable states. However, the one associated with the Robin BC
is more favourable because it corresponds to a smaller interface tension. Ефекти скiнченного розмiру у двох вiдокремлених конденсатах Бозе-Ейнштейна, обмежених твердою
стiнкою, дослiджено з допомогою рiвнянь Гросса-Пiтаєвского в наближеннi подвiйної параболи. Виходячи з узгодженостi мiж граничними умовами, якi накладаються на конденсати в обмеженiй геометрiї i
в повному просторi, ми знаходимо усi можливi граничнi умови разом iз вiдповiдними профiлями конденсату i мiжфазовi натяги. Нами вiдкрито два ефекти скiнченного розмiру: a) основний стан, отриманий
з граничної умови Ньюмана, є стiйким, а основнi стани, отриманi з граничних умов Робiна i Дiрiхлє, є
нестiйкими, b) отже, однаковим чином проявляються два можливих переходи змочування як результат двох нестiйких станiв. Проте, перехiд, пов’язаний з граничними умовами Робiна, виявляється бiльш
сприятливим, тому що вiн вiдповiдає меншому мiжфазовому натягу.